2016
DOI: 10.1051/epjconf/201613001003
|View full text |Cite
|
Sign up to set email alerts
|

Pentaquarks and doubly heavy exotic mesons

Abstract: Abstract. I discuss the experimental evidence for and theoretical interpretation of the new mesons and baryons with two heavy quarks. These include doubly-heavy baryons, exotic hadronic quarkonia and most recently a manifestly exotic pentaquark-like doubly heavy baryon with a minimal quark content uudc discovered by LHCb, whose mass, decay mode and width are in agreement with a prediction based on a physical picture of a deuteron-like Σ cD * "hadronic molecule". This strongly suggests a parallel with X(3872), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For recent reviews on the experimental properties of tetraquark candidates and their theoretical interpretations, we refer the reader to Refs. [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…For recent reviews on the experimental properties of tetraquark candidates and their theoretical interpretations, we refer the reader to Refs. [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This heavy diquark-anti-quark supersymmetry allows for mass relations not only between heavy baryons and mesons such as Qq and QQq, but also between heavy baryons and tetraquarks with hidden heavy flavor such as Qqq and Q Q qq. The recent quark model estimates for this last state are remarkable [27,28]. It is suggested that for a compact b b qq tetraquark, the binding energy is significant and about 200 MeV.…”
Section: Introductionmentioning
confidence: 99%